DETERMINATION OF TEMPERATURE DURING DEPTH GRINDING AND CONDITIONS FOR ITS DECREASE - Feodor NOVIKOV; Cătălin IANCU; Vladimir POLYANSKY; Yury GUTSALENKO (Fiabilitate şi Durabilitate)
A theoretical analysis of the conditions for reducing the temperature of grinding has been carried out and it has been shown that temperature of deep grinding is greater than under conventional multi-pass grinding with the same processing capacity. It is possible to reduce the temperature of deep grinding by increasing the cutting ability of the wheel and providing abundant heat removal from the cutting zone by using coolant, as well as reducing the speed of the wheel to reduce the friction intensity in the cutting zone. With a significant increase in the speed of the wheel (to values of 300 m/s), the main part of the heat released in the cutting zone is carried away with chips, and the grinding temperature decreases. This allows efficient use of deep grinding scheme. It is theoretically established that in this case the heating temperature of the chips is determined solely by the conditional cutting stress. Therefore, reducing it can reduce the temperature of grinding. The obtained results of theoretical studies were used to create a highperformance technological process of diamond electro-erosive grinding (diamond-spark grinding) of cutting multiblade carbide tools with elevated grinding depths (up to 0.6 mm) and a relatively low part speed (0.5 ... 1 m / min). This ensures the high quality of the surfaces to be treated (there are no burns, microcracks and other temperature defects).